Features of ophthalmoneuroprotection in patients with open-angle glaucoma in combination with diabetic retinopathy - O. I. Borzunov (Oftalʹmologiâ, 2014)
Aim: of this study is to evaluate ophthalmoneuroprotectional treatment of patients with POAG and diabetes mellitus type II in a specialized hospital. Material and methods: We have performed retro — and prospective analysis of the combined treatment of 130 patients (248 eyes) with a combination of primary open-angle glaucoma and diabetic retinopathy. Evaluation of the effectiveness of treatment was conducted on the following criteria: the severity of the hypotensive effect, the degree of improvement and duration of remission of major ophthalmic indicators. The patients were divided into four clinical — homogeneous groups: primary — 40 people (77 eyes), the comparison group I — 37 persons (71 eyes), the comparison group II — 33 people (60 eyes), the control group — 20 people (40 eyes). Results: Combination of different treatment strategy of laser and conservative treatment was tested. The result has been designed for optimal balance improving performance and reducing ocular side effects. Retinalamin ® 5 mg parabulbare number 10, Tanakan 1 tablet 3 times a day — 3 months. The optimal timing of re-treatment (at least 1 time in 9 months), in the case of significant progression of glaucomatous optic neuropathy — the timing is solved individually.